Archimedes Optimization Algorithm to Solve Multi-objective Optimal Power Flow in Hybrid AC-DC Power System - Patel, Chintan Dalsukh; Malakar, Tanmoy; S, Sreejith (2025 IEEE International Conference on Computer, Electronics, Electrical Engineering & their Applications (IC2E3), 2025)
Across the globe, a number of high voltage direct current (HVDC) links are installed, converting the grids into hybrid AC-DC power systems. Further, the reported studies on the optimum operation of such systems are limited to the optimal power flow (OPF) formulated as a single objective only. However, the operation of modern power systems needs to be carried out keeping multiple aspects in mind. Hence, this article presents the multi-objective OPF framework for hybrid AC-DC systems, formulated by taking conflicting objective functions like active power loss, generation cost, and emission. Two case studies are performed on a modified IEEE 30 bus system with Archimedes optimization algorithm (AOA) as an optimization tool. The performance of AOA is investigated by comparing the various pareto front quality indicators like spacing (SP), diversity matric (DM), and hypervolume (1/HV) with other optimization methods. In Case-1, an average reduction of 100.69 % and 30.58 % are reported for DM and SP, respectively.